2013
DOI: 10.1371/journal.pone.0053953
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamics of Distraction: Competition among Auditory Streams Modulates Gain and Disrupts Inter-Trial Phase Coherence in the Human Electroencephalogram

Abstract: Auditory distraction is a failure to maintain focus on a stream of sounds. We investigated the neural correlates of distraction in a selective-listening pitch-discrimination task with high (competing speech) or low (white noise) distraction. High-distraction impaired performance and reduced the N1 peak of the auditory Event-Related Potential evoked by probe tones. In a series of simulations, we explored two theories to account for this effect: disruption of sensory gain or a disruption of inter-trial phase con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
(90 reference statements)
4
10
1
Order By: Relevance
“…On the other hand, a stimulus-dependent oscillatory phase may serve as a gate of inputs, which underlies the formation and disruption of stimulus perception [18], [19]. The inputs with a ‘proper’ phase lead to signal amplification in the cortex, whereas those with an ‘improper’ phase lead to suppression [20].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a stimulus-dependent oscillatory phase may serve as a gate of inputs, which underlies the formation and disruption of stimulus perception [18], [19]. The inputs with a ‘proper’ phase lead to signal amplification in the cortex, whereas those with an ‘improper’ phase lead to suppression [20].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Giraudet, St‐Louis, Scannella, and Causse () reported auditory P300 amplitude reduction during the difficult flight simulation task. Consistent with these results, additional studies using EEG, MEG, and electrocorticography (ECoG) have also found attention to modulate auditory N100 amplitude (Molloy et al, ; Neelon, Williams, & Garell, ; Ponjavic‐Conte, Dowdall, Hambrook, Luczak, & Tata, ; Ponjavic‐Conte, Hambrook, Pavlovic, & Tata, ) and in some cases auditory P200 amplitude (Neelon et al, ) and P300 amplitude (Molloy et al, ) as well. In general, attention is thought to increase the magnitude of the peak of the N100 ERP component (Hillyard, Hink, Schwent, & Picton, ; Näätänen, Teder, Alho, & Lavikainen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Facilitation and disruption of oscillation is modulated in part by functional connectivity to brain regions involved with attention (Marshall, O'Shea, Jensen, & Bergmann, ). Many studies have implicated ITC (phase synchrony) in attentional and perceptual processing (Busch et al, ; Busch & Van Rullen, 2019; Calderone et al, ; Hanslmayr et al, 2007a,2007b; Hanslmayr, Gross, Klimesch, & Shapiro, ; Hanslmayr, Volberg, Wimber, Dalal, & Greenlee, ; Low & Strauss, ; Mathewson, Gratton, Fabiani, Beck, & Ro, ; Mathewson et al, ; Ponjavic‐Conte et al, ; VanRullen et al, ; Yamagishi, Callan, Anderson, & Kawato, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations